A Strategic Approach of Exhibition in Bangkok to Promote and Generate the Potential of MICE Industry in Thailand - Kampangseree, Adithep; Wongmonta, Seri; Techakana, Jusana (Dusit Thani College Journal, 2020)
This research objectives were 1) to promote the exhibition business in Bangkok and strengthen the potential of exhibition industry in Thailand; 2) to generate a strategic approach of exhibition to enhance in MICE Business of Thailand. It was a qualitative research using in-depth interviews with key stakeholders in the exhibition industry. The results found that: 1) Bangkok has the potential in organizing exhibitions as it is the hub and capital of Thailand; 2) The possibility to propose a strategic approach of exhibition to enhance in MICE Business of Thailand, which leads to 4 strategies namely: 1) to develop and encourage Bangkok in organizing exhibitions to be in the top 3 of ASEAN, 2) to strengthen the capacity to complete exhibitions in Bangkok; 3) to develop the exhibition marketing in Bangkok; and 4) to build the sustainability of exhibitions in Bangkok. As a result, the exhibitions in Bangkok are effective and have been accepted from all participants in the global arena.